Analisis Pengembangan Business Model Canvas Dalam Upaya Meningkatkan Keunggulan Bersaing Pt. Xyz. - Budiarto Budiarto (Universitas Tarumanagara, 2019)
The purpose of this research is to analyze various opportunities and threats obtained from the external environment and various strengths and weaknesses that PT XYZ has obtained from the internal environment which can be a reference for determining the company's business strategy. The external environment covers the general environment (macro) by using PESTEL Analysis (political, economy, social, technology, environment, legal) and also the industrial environment, using the Five Forces Porter analysis. The internal environment uses Core Competencies analysis with the VRCN criteria (Valuable, Rare, Costly to Imitate, Non-Substitutable). The combination of analyst results obtained from the external environment and internal environment will be able to provide an overview of the company's condition which will be simplified by the SWOT Matrix method and the Strategic Generic Porter. It is suggested that PT XYZ conducts market penetration outside the IPC group by developing end-to-end supply chain management product solutions by offering new model business patterns such as revenue sharing and manage operation by making product innovations that are in line with current technological needs.